2015
DOI: 10.3109/23744235.2015.1018316
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cytomegalovirus infections and glycoprotein B genotypes in live-born infants: a prevalence study in Turkey

Abstract: The study results suggest that the majority of congenital CMV infection in Turkey occurs following nonprimary maternal infection. We believe that congenital CMV infection and its long-term effects have been underestimated in our country, as infected infants are usually asymptomatic at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
1
12
1
15
Order By: Relevance
“…In comparison with developing countries with high maternal CMV seroprevalence, the frequency of cCMV infection that we found in the current study is in agreement with recently reported rates of infection from Brazil (0.6%) and China (0.7%), but in contrast to one report from Turkey (1.9%) ( 16 18 ). Differences in socioeconomic status and public health levels as well as ethnicity variations within populations, probably justify some of these reported differences between studies ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…In comparison with developing countries with high maternal CMV seroprevalence, the frequency of cCMV infection that we found in the current study is in agreement with recently reported rates of infection from Brazil (0.6%) and China (0.7%), but in contrast to one report from Turkey (1.9%) ( 16 18 ). Differences in socioeconomic status and public health levels as well as ethnicity variations within populations, probably justify some of these reported differences between studies ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…The 0.7% congenital CMV infection prevalence that we report from China is significantly lower than that reported in 2 other large studies with good ascertainment methods conducted in populations with high seroprevalence in Brazil (1.1%, n = 8047, P = 0.003) and Turkey (1.9%, n = 944, P < 0.001). [ 11 , 22 ] The population we examined in China had much less exposure to young children (<7% in current study) than other populations as a result of China's unique 1-child policy. This is consistent with the lower IgM seroprevalence previously reported in China (0.5%) compared to Brazil (2.3%) among females of reproductive age.…”
Section: Discussionmentioning
confidence: 90%
“…Dünyada bu konuda farklı coğrafi bölgelerde ve farklı hasta gruplarında CMV gB genotiplerinin araştırıldığı çalışmalar yapılmaktadır [8][9][10] . Ülkemizde bu konudaki çalışmalar sınırlı olup, sadece yenidoğanda yapılmış tek bir çalışma bulunmaktadır 11 . Böbrek, kök hücre ve kalp transplant alıcılarını kapsayan bir çalışma henüz yapılmamıştır.…”
Section: Introductionunclassified
“…RFLP ile genotiplendirme yapılan 15 örneğin DNA , en sık olarak saptanan genotipler olarak bulunmuştur. Ülkemizde bu konuda yapılmış ulaşabilen tek çalışmada Şahiner ve arkadaşları11 konjenital CMV enfeksiyonu olan 18 bebekte %83.3 oranında gB1 genotipi saptamışlardır. Bizim çalışmamızda ise, 13 yenidoğanda saptanan genotipler sırasıyla gB1 (%38.4), gB3 (%30.8), gB2 (%15.4) ve gB4 (%7.7) olmuştur.…”
unclassified